Prevalence of leptospirosis among soldiers: A systematic review. - Pavlo Petakh; Valentyn Oksenych; Oleksandr Kamyshnyi (PLoS Neglected Tropical Diseases)
Leptospirosis is a bacterial disease that spreads through water and soil contaminated with infected animal urine. Soldiers have a higher risk of infection because they often work in wet and muddy conditions. This systematic review examines how common leptospirosis is among military personnel. Studies published between January 2000 and November 2024 were collected from PubMed, Web of Science, and Scopus, following PRISMA guidelines. The review included studies that used laboratory tests to confirm leptospirosis cases in soldiers. Out of 67 studies, three met the inclusion criteria. These studies were conducted in Malaysia, Hawaii, and Honduras, with sample sizes between 488 and 1,000 soldiers. The infection rate ranged from 1.4% to 16.2%, with higher rates in tropical regions. Leptospirosis is often underdiagnosed in military personnel because symptoms are similar to other diseases, and testing is not always available. More awareness, better protective measures, and improved laboratory tests are needed to prevent infections. This review highlights the importance of better surveillance and health strategies for soldiers at risk of leptospirosis.